Penerapan Strategi PAKEM terhadap Kemampuan Menulis Karangan Deskriptif pada Siswa Kelas IV SDN 52 Kota Bengkulu - Dian Febriani; Resnani Resnani; Victoria Karjiyati (Universitas Bengkulu, 2018)
The purpose of this research is to know the Application of Active, Creative, Effective and Joyful Learning Strategy (PAKEM) to Descriptive Writing Ability of 4th Grade Students of SD Negeri 52 Kota Bengkulu. This type of research is quantitative research. The research method used is Quasy experience, by using 'matching only pretest-posttest control group design' design. Subjects in this study are the fourth graders of SD Negeri 52 Kota Bengkulu. The research instrument used is descriptive writing writing test. Data of this research are analyzed by using descriptive and inferential statistic analysis that is t-test. The result showed that the average value of posttest result in both classes was in the experimental class of 75.56 and the control class was 71.40. Based on t-test results obtained t count is 2.552 larger than ttable is 2.021 means Ha accepted. From these results it can be concluded that there is influence in the application of PAKEM strategy to the ability to write descriptive essay of fourth grade students of SD Negeri 52 Kota Bengkulu.